Penerapan Disiplin Kerja Pada Kepanitiaan Fairplay Danceground Competition 2024 Melalui Komunikasi Organisasi - Keishia Tania Aulia; Putu Indah Dianti Putri; Putri Ekaresty Haes; Putu Suparna (Journal of Innovative and Creativity, 2025)
The Fairplay Danceground Competition organized by the Hypehope Dance Bali community is known for its transparent judging system, yet the success of the event also relies heavily on organizational communication and the work discipline of the committee. This study aims to analyze how organizational communication shapes the committee’s work discipline using Karl Weick’s organizing theory. A descriptive qualitative approach was employed with purposive sampling, involving in-depth interviews with core committee members, supporting committee members, and participants, complemented by field observations during the event. Data were analyzed using Weick’s organizing model and validated through source triangulation. The findings show that the committee’s work discipline is formed through enactment, manifested in preventive, corrective, and adaptive actions such as arriving early, conducting repeated briefings, and responding quickly to technical issues; selection, seen in the choice of communication strategies such as briefings, the use of rundowns, a single-gate information system, and paired job assignments to reduce ambiguity; and retention, reflected in work patterns, coordination mechanisms, and problem-handling procedures that have been consistently replicated over the years. Participants perceived the committee as disciplined, professional, and capable of maintaining smooth event execution through clear and structured communication. These findings affirm that directed and continuous organizational communication serves as the fundamental basis for establishing work discipline within the Fairplay Danceground Competition 2024 committee.